JARGON IN THE ROLE OF MEANS OF MAKING JOURNALISTIC TEXTS INTIMATE (ON THE MATERIAL OF THE PUBLISHED MASS MEDIA OF 2016-2018) - Dumchak , I. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
In the article the intimization is considered to be a stylistic device by which the author tries to get closer to the reader, the listener. The attention is drawn to slang as one of the means of intimization, the functions of jargon and the reasons for its use in the media have been analyzed.